The notion of "afept" as a sabotage of the relationship between philosophy and literature - Asensi Pérez, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The creation of the neologims “afept” comes to question the difference between philosophy and literature in the sense of the metaphysical tradition. Although  it is no posible to sum up that two fields in only one name, because both have a lot of variety, philosophy has always tried to mark the distances in relation to literature. Our subject explains, through a close reading of Mukarovsky’s theory of the aesthetic function, and taking into account the tradition that it inaugurated, the reason why the “afept”, one of the main concepts of the criticism as sabotaje or the theory of world’s model, reveals the epistemologic power of literatura, and that it can be the source of the truth, even if it is negative. We use the Juan Ramón Jiménez’s poem “El viaje definitivo” as a guide for our argument.
Keywords: Criticism as sabotage; Theory of the world's model; philosophy and literature; Juan Ramón Jiménez